Pengaruh Information Quality, Product Variety Dan Delivery Service Terhadap Kepuasan Konsumen - Kurniawati, Dyah (JIMEK : Jurnal Ilmiah Mahasiswa Ekonomi, 2025)
The purpose of this study was to determine the effect of information quality, product variety and delivery service on marketplace user consumer satisfaction Sociolla in Indonesia. This type of research is a quantitative research population of Indonesian people who make transactions on the marketplace Sociolla. This study used purposive sampling with a number of samples 186 respondents.. Data analysis technique using multiple regression to test the hypothesis using the t test. Results research shows that information quality and product variety significant effect in a positive direction on user consumer satisfaction the Sociolla marketplace in Indonesia, while the delivery service has no significant effect but has a positive direction towards consumer satisfaction using the Sociolla marketplace in Indonesia.